Peran Manajemen Strategis dalam Meningkatkan Daya Saing Usaha Mikro Di Era Digital - Silviana Batubara (Indo Publishing, 2025)
Digital transformation has significantly reshaped the global business landscape, including for micro-enterprises that are now required to be more adaptive and strategic in their operations. This study aims to analyze the role of strategic management in enhancing the competitiveness of micro-enterprises in the digital era. A descriptive qualitative method was employed, using a case study approach involving ten micro-entrepreneurs in the cities of Medan and Yogyakarta. Data collection techniques included in-depth interviews, direct observations, and documentation, analyzed using the Miles and Huberman model. The findings reveal that the adoption of digital strategies—such as the use of social media, e-commerce platforms, and financial management applications—has significantly improved operational efficiency and market reach. However, challenges remain, including low digital literacy, lack of formal strategic planning, and limited access to managerial training. The study recommends strengthening digital business strategy capacities through cross-sectoral collaboration to build a competitive and sustainable micro-enterprise ecosystem in the era of digital transformation.